Patient Perceptions of Acute Phases of Rehabilitation Following Shoulder Arthroplasty - Elizabeth Horrall Stith; Lisa Borrero; Laura Santurri; Lori Breeden; Sarah Shemanski (Scholarworks @ WMU, 2020)
Background: Shoulder arthroplasty is a common procedure, but a lack of research regarding recovery and rehabilitation limits occupational therapists from providing appropriate education and support. The purpose of this study was to explore and understand the patient's experiences in the acute recovery phase following shoulder arthroplasty. Method: Twelve participants completed three semi-structured interviews in the first 6 weeks following surgery. A basic-interpretive approach was used before coding interview transcriptions into categories. Results: The participants initially reported increased reliance on assistance and/or modifications in ADLs routines, such as dressing, bathing, and sleep. Interruption in sleep was reported because of pain and/or positioning restrictions, and frustration because of a lack of sleep and need for assistance was noteworthy. As sling usage decreased, the participants reported returning to ADLs with a coinciding reduction in frustration. Finally, the participants noted improvement in ADLs and IADLs and a return to tasks such as driving, cooking and meal preparation, and returning to social engagements. Overarching themes included presurgical expectations, advice, pain reduction, and general improvement in quality of life. Discussion: Changes to patient education, including ADLs and IADLs assistance needs, may improve patient recovery. Occupational therapists specifically may improve recovery by using their understanding of arthroplasty, environment, routines, and other factors that affect sleep.